Thermoanalytical Properties of Hydrazinium Sulfite Monohydrate - S. Budkuley, Jayant (Asian Journal of Chemistry, 2010)
Hydrazinium sulfite monohydrate has been isolated as the product of the heterogeneous reaction between N2H4.H2O and SO2 gas. The product is characterized by chemical analysis, infrared spectrum, X-ray diffraction and thermoanalytical properties studies.